Handbook of Leaving Religion - Enstedt, Daniel; Larsson, Göran 1970-; Mantsinen, Teemu T. ([Erscheinungsort nicht ermittelbar] Brill, 2019)
The Handbook of Leaving Religion introduces a neglected field of research with the aim to outline previous and contemporary research, and suggest how the topic of leaving religion should be studied in the future. Readership: All interested in conversion, deconversion and apostasy processes, and anyone concerned with methodological and theoretical questions related to leaving or changing religion
English
Keywords: Apostasy; Conversion; Apostasy -- Case studies; Conversion -- Case studies; Blasphemy, heresy, apostasy; Apostasie; Conversion; Apostasie - Études de cas; Conversion - Études de cas; Religion; RELIGION / Blasphemy, Heresy & Apostasy; Apostasy; Conversion; Case Studies